El “terrorista” ante el Derecho penal: por una política criminal intercultural - Paredes Castañón, José Manuel (2013)
In the modern history of Western Civilisation, the term “terrorism” has been used without the appropriate care, making it a very vague and diffuse one. On the other hand, a more precise concept –which is similar to the partisan described by Carl Schmitt- is proposed than the one used by the media and the governments. And also is offered a non special treatment to the acts executed by subversive armed forces because their acts are no different to common felonies and States frequently give them a special characteristic to use the «Enemy’s Criminal Law» to normalise populations. Finally to legitimate an exceptional use of Criminal Law over terrorism and environment of dialogue and tolerance is suggested.En la historia moderna de la civilización occidental, el término “terrorismo” ha sido utilizado sin escrúpulos, haciéndolo bastante vago y difuso. En contraposición, se propone un concepto –cercano al de partisano de Carl Schmitt- más concreto y objetivo que el utilizado por los gobiernos y por los medios. También se propone que no se dé un trato excepcional a los delitos llevados a cabo por fuerzas subversivas armadas porque sus actos no son diferentes a los delitos comunes aunque los Estados modernos suelan asignarles una tipificación especial, para utilizar el llamado Derecho Penal del Enemigo en la normalización de las poblaciones. Finalmente, se sugiere un ambiente de diálogo y tolerancia para legitimar un verdadero uso excepcional del Derecho Penal sobre el terrorismo